Effect of Waste Brick Clay Powder on Self Compacted Concrete (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This research investigates the effect of waste clay bricks powder in producing self-compacting concrete by partial replacement of cement. Bricks were crushed to particle sizes smaller than 75 microns. Percentages of cement of 5, 10 and 12.5 % by weight were replaced by the power at w/c ratios of 0.4, 0.425 and 0.45. Fresh concrete workability then measured and hard concrete properties were determined at 28 days. The results show that waste bricks powder can be utilized partially instead of cement to produce concrete with self leveling fresh properties and good hard properties. Consequently, this proves that waste bricks can be recycled to minimize both the effect of waste material on the environment and the heat needed for cement production.